Ventilated tunnel solar dryers for small-scale farmers communities: Theoretical and practical aspects. Issue 10 (26th July 2016) - Talbot, P.; Lhote, M.; Heilporn, C.; Schubert, A.; Willaert, F.-X.; Haut, B.
ABSTRACT: The design of so-called "ventilated tunnel solar dryers" is presented in this work under theoretical and practical aspects. These dryers consist in a tunnel with a black floor and a plastic top, ventilated with fans supplied by a photovoltaic module. Along this tunnel, the air first passes through a heating part, which is product free and where the air is heated due to greenhouse effect. It then enters the second part of the dryer, the drying part, where the products to dry are spread. A rational and general design procedure based on the solving of energy and mass balance equations is developed and followed. This procedure allows designing the ventilation system and calculating the lengths of the heating and the drying parts of a dryer according to a scope statement and to design conditions insuring an efficient and homogeneous drying. Two dryers were designed, built and operated, in the frame of two development aid programs, in Cambodia and in Uganda. The fieldwork highlighted the importance of practical building and operating aspects, reported in the present paper, and of including people of the local communities in these programs. Results of field drying experiments are shown and demonstrate the validity of the design procedure. In particular, the validity of the energy balance equations at the basis of the procedure is demonstrated.